Identification of Adolescent Reproductive Health Information Needs Using The Perspective of Adolescents With A Pregnancy Experience - Herlin Fitriani Kurniawati; Herlin Fitriana Kurniawati (Jurnal Kebidanan, 2022)
Adolescence is a transitional period from childhood to adulthood. During this period, both physical and psychological conditions change. Adolescent pregnancy causes a higher risk for negative outcomes in terms of both physical and psychosocial aspects to the pregnant girl, baby, and husband. The research aimed to identify information needs for adolescent reproductive health using the perspective of adolescent with a pregnancy experience. The research used a qualitative design. The results of the study were divided into three themes, namely knowledge of adolescent reproductive health, access to reproductive health information, and reproductive health service providers. All the informants were under 20 years of age. In terms of education, most of the informants did not graduate from high school; even some of them graduated only from elementary school. In terms of knowledge about adolescent reproductive health, it was shown that adolescents did not have a comprehensive understanding of reproductive health, including reproductive organs and the process of pregnancy. Most of the informants thought that reproductive health was the health condition related to only the genital organs. They felt embarrassed to ask questions to their parents and they wanted to try something new. In terms of access to adolescent reproductive health services, access to information about reproductive health was still limited and there was a lack of information about how to access information about reproductive health. In addition, all of the informants said they did not know other programs due to lack of publications. Meanwhile, in terms of information needs for adolescent reproductive health, all the informants mentioned the need for information about adolescent reproductive health. These informants said that the presence of adolescent reproductive health information could prevent adolescent pregnancy. In terms of service recommendation, it can be in the form of continuous socialization at schools by teachers and health workers as well as consulting services at schools or at health centers.